Secondary antibody response of carabaos (Bubalus bubalis Linn.) immunized with autogenous hemorrhagic septicemia vaccine - Camer, Gerry A.; Torres, Ma. Immaculada P. (2006)
Hemorrhagic septicemia, an acute respiratory disease mainly affecting cattle and carabaos, can be controlled by programmed vaccination. An autogenous hemorrhagic septicemia vaccine was produced and primarily tested for carabaos in Northern Samar, Philippines. This study was the second phase of vaccine testing. A group of carabaos vaccinated initially with aluminum hydroxide gel adjuvanted - autogenous hemorrhagic septicemia (ALOH-AAHS) and double emulsion adjuvanted - autogenous hemorrhagic septicemia (DE-AAHS) vaccine preparations in Barangays Makiwalo and San Agustin, Northern Samar was given a booster dose of the vaccines. Secondary immune responses were measured by enzyme-linked immunosorbent assay (ELISA) and passive mouse protection test (PMPT). A highly significant antibody rise following booster shot was observed in the sera of carabaos treated with ALOH-AAHS (p0.05) after secondary immunization. This result was attributed to the remarkably high antibody level maintained by the DE-AAHS treated group prior to booster vaccination. Passive mouse protection testing resulted in a standard passing rate for both types of vaccine preparations (Bureau of Animal Industry standard passing protection rate: 80%). The ALOH-AAHS and DE-AAHS vaccines are therefore recommended for semi-annual and annual vaccination programs, respectively. Cross-protection tests, continuous monitoring and programmed use of autogenous hemorrhagic septicemia vaccine for carabaos in the province of Northern Samar are recommended.
Keywords: Water buffalo; Antigens and antibodies